A Short Review of Organic Nanofluids: Preparation, Surfactants, and Applications - Deb Majumder, Samarpan; Das, Ankit (Frontiers in Materials, 2021)
Recently, there has been significant advancement in efforts toward achieving zero-energy buildings. It is quite evident that the HVAC systems consume a considerable percentage of the total energy consumption of a building; therefore, making them sustainable is of the utmost importance. Nanofluid serves as a simple, yet innovative, approach in decreasing the power consumption of the HVAC systems by improving the thermophysical properties of the coolants and enhancing heat transfer. As a result, this has attracted the attention of many researchers across the globe. This manuscript reviews the different preparation methods of nanofluid, surfactants used in stabilizing the nanofluid, and the different areas in which it can be used.